Marine-derived fungi: diversity of enzymes and biotechnological applications - Bonugli-Santos, Rafaella C.; dos Santos Vasconcelos, Maria R.; Passarini, Michel R. Z.; Vieira, Gabriela A. L.; Lopes, Viviane C. P.; Mainardi, Pedro H.; dos Santos, Juliana A.; de Azevedo Duarte, Lidia; Otero, Igor V. R.; da Silva Yoshida, Aline M.; Feitosa, Valker A.; Pessoa, Adalberto; et al. (Frontiers in Microbiology, 2015)
The ocean is considered to be a great reservoir of biodiversity. Microbial communities in marine environments are ecologically relevant as intermediaries of energy, and play an important role in nutrient regeneration cycles as decomposers of dead and decaying organic matter. In this sense, marine-derived fungi can be considered as a source of enzymes of industrial and/or environmental interest. Fungal strains isolated from different substrates, such as invertebrates, decaying wood, seawater, sediments and mangrove detritus, have been reported to be producers of hydrolytic and/or oxidative enzymes, with alginate lyase, amylase, cellulase, chitinase, glucosidase, inulinase, keratinase, ligninase, lipase, nuclease, phytase, protease and xylanase being among the enzymes produced by fungi of marine origin. These enzymes present temperature and pH optima ranging from 35 to 70 ºC, and 3.0 to 11.0, respectively. High-level production in bioreactors is mainly performed using submerged-state fermentation. Certain marine-derived fungal strains present enzymes with alkaline and cold-activity characteristics, and salinity is considered an important condition in screening and production processes. The adaptability of marine-derived fungi to oceanic conditions can be considered an attractive point in the field of fungal marine biotechnology. In this review, we focus on the advances in discovering enzymes from marine-derived fungi and their biotechnological relevance.